Thermodynamic analysis of the cascaded packed bed cryogenic storage based supercritical air energy storage system. (February 2019) - Lin, Xipeng; Wang, Liang; Xie, Ningning; Li, Guoyue; Chen, Haisheng
Abstract: This paper presents a thermodynamic analysis of a novel stand-alone supercritical air energy storage (SAES) system, based on cascaded packed bed cryogenic storage. This system has the advantages of low cost, high efficiency and safety thanks to the different grade cryogenic energy be transferred and stored in two cascaded packed beds. Thermodynamic analysis results show that the discharge pressure and roundtrip efficiency are influenced by component efficiencies, charge pressure and middle temperature, and the optimized charge pressure and middle temperature are 120.0 bar and -70 ° C, respectively, no matter how component efficiencies changes. The increasing liquid air storage pressure reduces the exergy loss in evaporator and condenser and improves the round trip efficiency. Results show that a high round trip efficiency, which is up to 65% could be obtained in this novel supercritical air energy storage system.